Effects of activated carbon ageing in three PCB contaminated sediments: Sorption efficiency and secondary effects on Lumbriculus variegatus. (15th November 2015) - Nybom, Inna; Waissi-Leinonen, Greta; Mäenpää, Kimmo; Leppänen, Matti T.; Kukkonen, Jussi V.K.; Werner, David; Akkanen, Jarkko
Abstract: The sorption efficiency and possible secondary effects of activated carbon (AC) (ø 63–200 μm) was studied with Lumbriculus variegatus in three PCB contaminated sediments applying long AC-sediment contact time (3 years). AC amendment efficiently reduced PCB bioavailability as determined with both, L. variegatus bioaccumulation test and passive samplers. However, dose related secondary effects of AC on egestion rate and biomass were observed (applied doses 0.25% and 2.5% sediment dry weight). The sorption capacity and secondary effects remained similar when the experiments were repeated after three years of AC-sediment contact time. Further, transmission electron microscopy (TEM) samples revealed morphological changes in the L. variegatus gut wall microvilli layer. Sediment properties affected both sorption efficiency and secondary effects, but 2.5% AC addition had significant effects regardless of the sediment. In, conclusion, AC is an efficient and stable sorbent to decrease the bioavailability of PCBs. However, sediment dwelling organisms, such as Oligochaete worms in this study, may be sensitive to the carbon amendments. The secondary effects and possible morphological changes in benthic organisms should not be overlooked as in many cases they form the basis of the aquatic food webs. Graphical abstract: Highlights: AC proved to be efficient and stable sorbent to decrease the bioavailability of PCBs. PDMS coated glass suited well to measure PCB bioavailability in AC amended sediments. AC induced morphological changes were seen in TEM figures in Lumbriculus variegatus gut wall. AC dose related adverse effects were observed on growth, reproduction and egestion rate.